A novel curtain design to enhance the aerodynamic performance of Invelox: A steady-RANS numerical simulation. (1st February 2019) - Anbarsooz, M.; Amiri, M.; Rashidi, I.
Abstract: Invelox is a patented structure designed to capture the incident wind from every direction, guide the collected wind to the ground level and increase its velocity. Previous numerical studies have revealed that a considerable portion of the collected wind escapes the structure from the opposite side of the wind entering Invelox. In the present study, three possible curtain designs are proposed to reduce or fully-eliminate this escaping air. The improved capability of Invelox to augment the wind velocity using these curtain systems is evaluated via numerical simulations. The results show that the best configuration can fully eliminate the escaping air and it will not disturb the air flow uniformity inside the Venturi section. On average, the best design can lead to a 25% increase in the average wind velocity inside the Venturi for the wind velocities of 3–12 m/s. The results also show that although it has been claimed that Invelox accepts wind from all directions, it can only be efficient at the incident wind directions of −90 to 90°. Increasing the turbulent intensity of the upcoming wind from 0 to 20%, however, has no considerable effects on the Invelox speed ratio. Highlights: Three curtain designs are proposed to improve the speed ratio of Invelox. The proposed modifications are studied numerically. The best modification eliminated all the escaping air from Invelox. On average, a 25% increase in the wind velocity inside the Venturi section is achieved. Invelox works efficiently for the incident wind direction of −90 to 90°.